Three new species of Stibeutes and Gnotus (Hymenoptera: Ichneumonidae) from holm-oak and cork-oak Mediterranean forests - Bordera, Santiago; Hernández-Rodríguez, Estefanía (Insect Systematics & Evolution, 2004)
The new species Stibeutes hirsutus, S. calderonae and Gnotus klausi from Spanish holm-oak and cork-oak woods are described and illustrated. Data on their habitat and the phenology of S. hirsutus are reported. The species S. breviareolatus collected in a cork-oak forest is recorded for the first time for Spain. New keys for the Gnotus tenuipes species group and for the Spanish species of Stibeutes are provided.
Keywords: Gnotus; habitat; morphology; new species; phenology (PG); Stibeutes

Three new species of Stibeutes and Gnotus (Hymenoptera: Ichneumonidae) from holm-oak and cork-oak Mediterranean forests (Insect Systematics & Evolution, 2004)
The new species Stibeutes hirsutus, S. calderonae and Gnotus klausi from Spanish holm-oak and cork-oak woods are described and illustrated. Data on their habitat and the phenology of S. hirsutus are reported. The species S. breviareolatus collected in a cork-oak forest is recorded for the first time for Spain. New keys for the Gnotus tenuipes species group and for the Spanish species of Stibeutes are provided.